Equity, the transnational and the global learning crisis - Hania Sobhy (Cogent Social Sciences)
This review article critically examines the role of political economy variables in shaping education policy in the context of a global learning crisis. It surveys the literature on how factors such as democracy, institutional arrangements, ideology, and transnational dimensions influence the promotion of equitable learning. The article assesses the role of these factors in the case of Egypt through a review of educational developments over the past three decades in a country that shares many challenges with low- and middle-income countries. Presenting novel data and key indicators on Egypt and a framework for analysing equitable learning elsewhere, the article maps the dimensions of the learning crisis that has developed in parallel to the adoption of a new global learning agenda supported by international agencies. The analysis suggests that democracy and institutional features are not robust explanatory variables for the adoption or successtion of effective education policy. Instead, the article shows how commitment to equity, patterns of privatization, and levels of international debt and development assistance are the critical elements of understanding the learning crisis.